Effect of thermal and mechanical treatments on corrosion of API X-52 grade line pipe steel in flowing 3.5% NaCl solution - Amarnath; Upadhyay S.N.; Namboodhiri T.K.G. (My University, 2025)
Commercial API X-52 grade line pipe steel was studied for its corrosion resistance in 3.5% NaCl solution under static and dynamic conditions. Heat treatments and cold rolling resulted in considerable variations in mechanical properties and microstructure of the steel. These treatments resulted in insignificant changes in static corrosion rate, whereas considerable variations in corrosion rate were observed under dynamic conditions. Quenched and tempered steel showed the maximum corrosion resistance and annealed steel showed the minimum resistance under dynamic conditions.